Absence and light : meditations from the Klamath Marshes - Campbell, John R., 1957- (Environmental arts and humanities series., 2002)
""In order to accept the enormous responsibility that comes of being in the world, we must first conceive, in spite of all the obstacles, the state of actually being the world." It is for this reason that John R. Campbell came to the Klamath marshes, a wetland in southern Oregon formed by three ancient, shallow lakes, a vast emptiness that is paradoxically home to an amazing diversity of life, of untold thousands of birds both migratory and resident, of all the interconnected life forms that make up one of North America's richest natural environments."